1995
DOI: 10.1152/ajpheart.1995.269.3.h877
|View full text |Cite
|
Sign up to set email alerts
|

Primary negativity does not predict dominant pacemaker location: implications for sinoatrial conduction

Abstract: Activation sequence maps derived during normal sinus rhythm from extracellular potentials in the canine right atrium exhibit widely separated sites of origin. The objectives of this study were to characterize the distribution of pacemakers within the right atrium and to determine the relationship of pacemaker action potentials to sites of earliest surface activation as well as to local extracellular electrograms. The right atria of six adult mongrel dogs were rapidly excised under deep pentobarbital sodium ane… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

7
40
0

Year Published

1998
1998
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 33 publications
(47 citation statements)
references
References 0 publications
7
40
0
Order By: Relevance
“…14 The complex connexin phenotypes in sinus node pacemaker cells may also explain, in part, the electrophysiological data of Bromberg et al, 47 who used floating microelectrodes to record action potentials from cells within the canine sinus node while simultaneously recording from multiple extracellular sites. They showed that although the earliest intracellular activation occurred within the central portion of the sinus node, the earliest extracellular activation occurred at the superior and inferior poles of the nodal region, suggesting discrete propagation exit sites from the node.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…14 The complex connexin phenotypes in sinus node pacemaker cells may also explain, in part, the electrophysiological data of Bromberg et al, 47 who used floating microelectrodes to record action potentials from cells within the canine sinus node while simultaneously recording from multiple extracellular sites. They showed that although the earliest intracellular activation occurred within the central portion of the sinus node, the earliest extracellular activation occurred at the superior and inferior poles of the nodal region, suggesting discrete propagation exit sites from the node.…”
Section: Discussionmentioning
confidence: 99%
“…Perhaps certain types of intercellular channels facilitate conduction between the pacemaker and atrial myocardium and correlate with the dispersed exit sites observed in our previous studies. 47 Other types of channels may subserve the electrotonic interactions that determine the final rate and site of the dominant pacemaker region within the sinus node and at the same time inhibit rapid impulse propagation or depolarization wave fronts within the pacemaker matrix. Answers to these questions will require more extensive electrophysiological and anatomic-biochemical studies in both dispersed cell aggregates and in vivo preparations.…”
Section: Discussionmentioning
confidence: 99%
“…Literature data are available from isolated pacemaker cells [17,33], cell clusters [14,17], and isolated right atrium preparations [4,5,7,22,35]. BI variability of pacemaker cells and cell clusters was mostly quantified by the coefficient of variation C BI = 100 SD BI BI --1 (given as a percentage) or related measures [6,14,17,33].…”
Section: Interbeat Interval Variability In the Sino-atrial Nodementioning
confidence: 99%
“…The earliest site of atrial endocardial or epicardial activation is not necessarily the actual location of the pacemaker [10]. These findings suggested that the SAN either: (i) consisted of multiple pacemakers that could entrain one another; or (ii) contained multiple exit sites from which atrial surface activation would first occur [8,9].…”
Section: San Electrophysiologymentioning
confidence: 99%